Medieval masculinities: Men disguised as women in the narrative of Yosef ben Me'ir ibn Zabarrah and Raoul de Houdenc - Lorca, Paulina (Cuadernos Judaicos, 2016)
Medieval literature presents countless male characters that tend to match heroic, chivalric or courtly character configurations, just to name a few. However, there are other masculinities, as in The Book of Delight by Yosef ben Me'ir ibn Zabara and Meraugis of Portlesguez by Raoul of Houdenc, where we find men who disguise themselves as women. Therefore, some questions arise, such as: Is transvestism in these texts subversive or not? Do the main characters challenge the canons of medieval beauty and masculinity? This paper seeks to visualize this kind of characters, while establishing a dialogue between Hispano-Hebrew and Romance fiction.